Multidimensional stoichiometric mismatch explains differences in detritivore biomass across three forest types - Zhang, Bing; Chen, Haozhen; Deng, Mingqin; Li, Xin; Chen, Ting-Wen; Liu, Lingli; Scheu, Stefan; Wang, Shaopeng (The Journal of animal ecology, 2023)
The ecological stoichiometry theory provides a framework to understand organism fitness and population dynamics based on stoichiometric mismatch between organisms and their resources. Recent studies have revealed that different soil animals occupy distinct multidimensional stoichiometric niches (MSNs), which likely determine their specific stoichiometric mismatches and population responses facing resource changes. The goals of the present study are to examine how long-term forest plantations affect multidimensional elemental contents of litter and detritivores and the population size of detritivores that occupy distinct MSNs. We evaluated the contents of 10 elements of two detritivore taxa (lumbricid earthworms and julid millipedes) and their litter resources, quantified their MSNs and the multidimensional stoichiometric mismatches, and examined how such mismatch patterns influence the density and total biomass of detritivores across three forest types spanning from natural forests (oak forest) to plantations (pine and larch forests). Sixty-year pine plantations changed the multidimensional elemental contents of litter, but did not influence the elemental contents of the two detritivore taxa. Earthworms and millipedes exhibited distinct patterns of MSNs and stoichiometric mismatches, but they both experienced severer stoichiometric mismatches in pine plantations than in oak forests and larch plantations. Such stoichiometric mismatches led to lower density and biomass of both earthworms and millipedes in pine plantations. In other words, under conditions of low litter quality and severe stoichiometric mismatches in pine plantations, detritivores maintained their body elemental contents but decreased their population biomass. Our study illustrates the success in using the multidimensional stoichiometric framework to understand the impact of forest plantations on animal population dynamics, which may serve as a useful tool in addressing ecosystem responses to global environmental changes.
Keywords: millipede; Animals; Forests; soil animal; land-use change; Biomass; Oligochaeta; Pinus; lesy; elemental content; členovci; Arthropods; earthworm; ecological stoichiometry; ekosystém; Ecosystem; stoichiometric niche; zvířata; Soil; půda; biomasa; borovice; biogeochemical